1999
DOI: 10.1099/13500872-145-6-1375
|View full text |Cite
|
Sign up to set email alerts
|

Lactococcus lactis contains only one glutamate decarboxylase gene

Abstract: Glutamate decarboxy~ase, which is associated with a glutamate-dependent acid-resistance mechanism, was purified from Lactococcus lactis subsp. lactis by a three-step procedure. The specific activity was increased about 114-fold with a yield of 16%. The N-terminal amino acid sequence of the enzyme was determined. The gene encoding this enzyme was cloned in kcherichia coli, and its nucleotide sequence was determined. The deduced amino acid sequence suggests that the enzyme is produced as a mature form (466 amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 26 publications
2
75
0
1
Order By: Relevance
“…Southern blot analysis of a number of strains of L. lactis subsp. lactis has shown gadB to be present in a single copy (166). A constitutively expressed gene, gadR, was found upstream.…”
Section: Mechanisms Of Resistancementioning
confidence: 98%
“…Southern blot analysis of a number of strains of L. lactis subsp. lactis has shown gadB to be present in a single copy (166). A constitutively expressed gene, gadR, was found upstream.…”
Section: Mechanisms Of Resistancementioning
confidence: 98%
“…It has been reported that gadB and gadC (encoding the antiporter that exchanges glutamate for GABA) form an operon structure in L. lactis. 20) At present, it is unknown whether gadC exists upstream of gadB in Lb. paracasei.…”
Section: Discussionmentioning
confidence: 99%
“…paracasei differed from that previously reported for GAD from other LAB. 18,20) The enzyme was active within a broad pH range as compared with GADs from other LAB species.…”
Section: Properties Of Gad In Lb Paracaseimentioning
confidence: 99%
See 1 more Smart Citation
“…lactis bv. diacetylactis 01-7 19 . Amplified products were electrophoresed using 1.5% (w/v) agarose for 20 min at 100 V. L. lactis subsp.…”
Section: Identification Methodsmentioning
confidence: 99%